Transient analysis of overhead transmission lines based on fitting methods - Colqui, Jaimis S.L. [UNESP]; Araújo, Anderson R.J.; Pascoalato, Tainá F.G. [UNESP]; Kurokawa, Sérgio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
JMarti model is one of the most employed overhead transmission line (OHTL) model for transient analysis. In this model, the characteristic impedance Zc and the propagation function H are fitted by Bode's method which uses pole-zeros form. However, another tool available is the Vector Fitting (VF) method which fits a frequency-dependent response into a rational function based on the pole-residue form. For the precise transient analysis, the ground-return impedance must be computed which various approaches have been proposed in literature. The Carson's approach assumes that the soil is modeled by a constant soil resistivity and by a relative permittivity εr equal to 1. However, Sunde's approach includes any value of the soil permittivity εr which comprises soils from dry to humid grounds. Based on these characteristics, this paper investigates the effects of the Sunde's approach in the JMarti model using the Bode's method and VF method to synthesize the rational functions implemented in the ATP-software. Simulation results show a better accuracy employing the VF method using lower number of poles to fit Zc and H. The Furthermore, the transient responses computed with Sunde's approach have presented lower voltage peaks in comparison with those computed with Carson's approach for different values of εr.
Keywords: Electromagnetic transients; Frequency dependence; Soil electrical parameters; Transmission lines